2019
DOI: 10.1073/pnas.1814700116
|View full text |Cite
|
Sign up to set email alerts
|

Gene activation precedes DNA demethylation in response to infection in human dendritic cells

Abstract: DNA methylation is considered to be a relatively stable epigenetic mark. However, a growing body of evidence indicates that DNA methylation levels can change rapidly; for example, in innate immune cells facing an infectious agent. Nevertheless, the causal relationship between changes in DNA methylation and gene expression during infection remains to be elucidated. Here, we generated time-course data on DNA methylation, gene expression, and chromatin accessibility patterns during infection of human dendritic ce… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
86
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(98 citation statements)
references
References 57 publications
10
86
0
2
Order By: Relevance
“…From the co-expression and co-methylation network perspective, it is still challenging to interpret as the DNA methylation play a very important role in regulating the gene expression. A recent study might support our finding, which suggested that DNA methylation would rather play a role in fine tuning gene expression regulation (64). And then by applying RegEnrich, we predicted a key regulator network which potentially play important roles in CXCL4-moDCs phenotyping.…”
Section: Discussionsupporting
confidence: 80%
“…From the co-expression and co-methylation network perspective, it is still challenging to interpret as the DNA methylation play a very important role in regulating the gene expression. A recent study might support our finding, which suggested that DNA methylation would rather play a role in fine tuning gene expression regulation (64). And then by applying RegEnrich, we predicted a key regulator network which potentially play important roles in CXCL4-moDCs phenotyping.…”
Section: Discussionsupporting
confidence: 80%
“…Thus, DNA methylation and differential expression did not correlate over time despite evidence of their association revealed by CpGOE values. DNA methylation and differential expression do not necessarily correlate throughout time when a causal relationship is present (Secco et al, 2015;Pacis et al, 2019), and have been documented to be unpaired during invertebrate development under high pCO 2 (Strader et al, in review). The relationship between DNA methylation and gene expression in molluscs has proved tenuous in some cases.…”
Section: Evidence Of a Role For Dna Methylation In Differential Exprementioning
confidence: 99%
“…Whereas the classical dogma is that gene methylation regulates gene expression, recent studies evidenced that DNA methylation changes may happen after changes in gene expression. Pacis et al identified lower DNA methylation level in dendritic cells post Mycobacterium tuberculosis infection, but the detectable losses in methylation occurred after the changes in gene expression, indicating the demethylation was a downstream consequence of transcriptional activation [107]. The results also suggested that DNA demethylation in response to infection could play a role in facilitating the binding of methylation-sensitive transcription factors (TFs) at enhancers and may relate to innate immune memory.…”
Section: Relationships Between Epigenetic Regulation and Gene Expressionmentioning
confidence: 99%